Testing Weak Form Market Efficiency and its Impact on Stock Valuation: Empirical Evidence from Stock Market in Bangladesh - Riyashad Ahmed; Delowar Hossain (Jurnal Ekonomi dan Studi Pembangunan, 2019)
The empirical study focus on the stock valuation with considering weak form efficiency where the objective is to find out the Bangladesh stock market is efficiency or not by testing the weak form efficiency. Here Daily trading price is used from 2011 to 2017 conceding daily index of Dhaka stock exchange and 38th leading company are considered to know the intrinsic price in the market. The CAPM model is used to find out the intrinsic value. we can reach a  result that if the market price of considering firm and intrinsic value is equal the market is efficient that means we a from efficient as only historical information  is reflected on the companies. We get the result that the Dhaka stock market is not efficient as the market price and intrinsic value is not equal. The arbitrage profit is possible. Keywords: Efficiency Market; Weak Form efficiency; Intrinsic Value; Undervalued and Overvalued.JEL Classification: G10, G11, G14